2010
DOI: 10.1016/j.visres.2010.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Uninformative visual experience establishes long term perceptual bias

Abstract: Visual appearance depends upon the resolution of ambiguities that arise when 2D retinal images are interpreted as 3D scenes. This resolution may be characterized as a form of Bayesian perceptual inference, whereby retinal sense data combine with prior belief to yield an interpretation. Under this framework, the prior reflects environmental statistics, so an efficient system should learn by changing its prior after exposure to new statistics. We conjectured that a prior would only be modified when sense data co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
4

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(60 citation statements)
references
References 33 publications
8
48
4
Order By: Relevance
“…In the new study the visual system was forced to resolve the ambiguity using a less reliable stereo signal, and to maintain the percept without the benefit of continued disambiguating information. Previous studies found that low-information stimuli can cause stronger learning [4], [17], [20] and cause learning to occur in cases where it did not occur otherwise [5]–[7]. The result from Experiment 1 confirms the potency of low-information stimuli in promoting the recruitment of difficult-to-learn cues.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…In the new study the visual system was forced to resolve the ambiguity using a less reliable stereo signal, and to maintain the percept without the benefit of continued disambiguating information. Previous studies found that low-information stimuli can cause stronger learning [4], [17], [20] and cause learning to occur in cases where it did not occur otherwise [5]–[7]. The result from Experiment 1 confirms the potency of low-information stimuli in promoting the recruitment of difficult-to-learn cues.…”
Section: Resultssupporting
confidence: 75%
“…The differences in learning due to controlled factors, such as the new signal to be learned, whether the session started with ambiguous trials [4], [17], [20], or whether the object was moving, were large; whereas effects are robust to changes in other factors, such as overall size of the display [4], [17], [20]. Factors that are intrinsic to the perceptual system play a role.…”
Section: Introductionmentioning
confidence: 95%
“…the perturbation experiment); on the other hand, state change seems to sometimes occur in total absence of external visual stimulation (the short-term temporal dynamics experiment). Results showing the importance of endogenous (43) and initial (44) perceptual decisions to subsequent cue learning may be germane to these issues.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, does the learning reflect the operation of a functionally useful mechanism, one that would normally act to improve perception, and thus the organism's fitness or “achievement” (Brunswik, 1954)? While one instance of long term learning cannot decide this question, the long-lasting nature of the learning is at least consistent with learning how to disambiguate an otherwise ambiguous visual stimulus so as to be prepared the next time it occurs, in the service of fast and accurate perception (Harrison & Backus, 2010b). …”
Section: Discussionmentioning
confidence: 99%